UJUNG SENJA PABRIK-PABRIK GULA DI BATAVIA AWAL ABAD KE-18 - Huddy Husin (Universitas Indraprasta PGRI, 2016)
Transitional forms of commodities in the international market from the beginning of spice to the sugarcane (sugar), tea, rubber and others responded by the colonial Dutch East Indies with a test and cultivation of plant species of the commodity. Sugarcane is one of the plants which are priorities for the Dutch East Indies colonial government to be managed and produki (although the number is still minimum scale), this attempt to force the colonial government to involve other communities, especially Tioghoa who have skills in managing sugarcane crop. Not only felt the sweet result of the production of sugar cane (sugar) but the journey also gives a lot of negative consequences such as criminal tendency and resistance to the colonial government conducted by the Chinese. This paper tries to explain how the effort to membangu industrialization of the sugar cane plant culminate in a social movement, then the direction of its development would benefit the colonial government. Through this article also hoped we can learn how the logical consequence of industrialization itself, and preparing for its development direction in order not to evolve towards a state that is destructive.Keyword :Sugar Factory, Batavia